Antigiardial effect of Anethum graveolens aqueous extract in children - Sahib, Ahmed Salih (J Intercult Ethnopharmacol, 2014)
BACKGROUND: Giardia lamblia is the most common intestinal parasite of humans identified worldwide. In spite of metronidazole (Met) is the most commonly used drug for the treatment of giardiasis in humans, low patient compliance and side-effects, especially in children encourage efforts to look for new and safe agent; many plants used in folk medicine thought to have antigiardial effect, Anethum graveolens (AG) (dill) is an annual herb cultivated in Iraq used both as a medicinal agent and as food spice. The aim of this study was to investigate the effect of aqueous extract (AE) of AG leave in the treatment of giardiasis, compared with that of standard drug Met. PATIENTS AND METHODS: A prospective randomized clinical trial was carried out on 28 pediatric patients of both sexes with age of <1 year ranging from 3 to 11 months, who attend to outpatient private clinic in Baghdad for a period of 6 months from June 2013 to December 2013,Patients participate in this study were allocated into two groups Group A composed of 14 patients treated with Met 15 mg/kg 3 times a day for 5 days. Group B composed of 14 patients treated with AGAE 1 ml 3 times a day for 5 days. Stool samples were collected at 0 time before administration of treatment, after 5 days and after 14 days from starting the treatments to check the efficacy of treatment. RESULTS: Administration of AGAE results in a significant decrease in incidence of G. lamblia after 5 days of treatment indicating the efficacy of AGAE in the treatment of giardiasis a result that is comparable to that of Met. CONCLUSION: This study showed that pediatric patients with giardiasis may benefit from 5 days treatment with AGAE administered as 1 ml 3 times daily, the improvement in the symptom with this herbal agent was comparable to the standard pharmacological agent Met; results showed that AG is safe and tolerable over treatment course.